Environmental Writing as a Humanitarian Response to Environmental Challenges - Filyanina, Nelya (Skhid, 2015)
In the article the phenomenon of environmental literature as a humanitarian response to the environmental challenges of our time. The role of literature in understanding the environmental challenges of our time belongs to the newest areas of research. Of particular note is highlighting the phenomenon of literature as a factor ekoeducation and environmental awareness. Ecological Literature, representing by different in form and genre texts in a specific way connects the science, education, philosophy, politics, promoting the entry of environmental ideas in the broad cultural field. Relatively modern ecological literature can be divided into the literature on wildlife and literature on the environmental crisis and catastrophe. First class literature combined under the title "nature writing", and to some extent continues the tradition of romanticism and naturalism, and describes the nature and tradition of thinking about nature. To describe second-class literature often use the term "environmental writing". On the one hand, it is rooted in the tradition of romanticism and naturalism on the other - aimed at the future, as it provides valuable guidance to people on nature conservation and environmental problems. In general, all these diverse body of texts can be divided into: texts belonging to "nature writing"; texts that combine the features of "nature writing" and "environmental writing" ("nature/environmental writing"); texts belonging to the "environmental writing". Texts of environmental literature generated in long observations of the natural world, the relationships in nature, for its integrity and, at the same time, awareness of the vulnerability of nature. Environmental literature proves the thesis of "the presence in the culture of science and culture in science." The phenomenon of environmental writing as a humanitarian reaction on environmental challenges of nowadays is considered. Environmental writing represented by texts of different forms and genres interconnects in a specific way science, education, philosophy, policy, promoting inclusion ideas about nature protection in the wide cultural field.